Análise de lajes maciças de concreto armado utilizando analogia de grelhas - Leite, Kamila (2017)
The present work presents the analysis of the bending moment and vertical displacement of a rectangular slab, differing in three types the bonding of its edges and, of a slab in L, set in all its sides. The purpose of this study is to verify, using tables and the grid analogy method, the influence of the conditions of support and refinement of the mesh of the equivalent grid used in the bending moments and the arrow of solid reinforced concrete slabs. The analysis by means of tables was performed using the authors Marcus and Bars, for the determination of the bending moment and the vertical displacement, respectively. On the other hand, the sizing by analogy of grids was done with the help of free software VGPlan, distributed free of charge by the University of São Paulo, to be used in an academic context. The results of bending and closing moment obtained for three slab configurations were compared with usual procedures of percentage difference, in which for the bending moment it was possible to perceive that there was greater variation between the table methods and grid analogy in the slab belonging to the case where two of the edges of the slab are set and the other two simply supported, for the negative moment in the x direction, having a difference of 18.6%, while the smallest discrepancy occurred in the case where all the edges of the slab are set, with 0.14% difference in the negative moment in the y direction. As for the vertical displacement or arrow analysis, the slab of the case where two edges are set and the other two supported, also presented the greatest difference between the values obtained by the two methods, being equal to 17.4%, while, for the case of the slab with four crimped edges, there was a difference of 0.04% between the two methodologies used. To perform an example of a non-rectangular slab, an L-slab was analyzed using the grid analogy - since the tables are restricted to use for rectangular slabs - from the results obtained it was realized that the values of bending moment and arrow, converged after 11 steps of refinement of the equivalent grid, with a spacing equal to 14 cm. After analyzing the results, it can be concluded that the grid analogy process is dynamic and allows to analyze a slab in different geometric situations. This method escapes the classical calculation of the use of tables, considering the interaction between the elements. In this way, the contribution of each element that composes the slab is correctly characterized, and the determined efforts tend to be more accurate and closer to the real values.